The Stigmatization of Arabic Language Radicalism-Terrorism, Religiosity, and Student Learning Motivation - Nasarudin Nasarudin (Universitas Islam Negeri Palangka Raya, 2023)
The stigma of Arabic as a radical language affects motivation, leading to disinterest in Arabic. This study aims to find out the relationship between the stigmatization of Arabic radicalism-terrorism and religiosity and the motivation to learn Arabic among students of Muhammadiyah Mataram University (UMMAT). It uses a quantitative approach with a type of correlation. The results of the partial test show that there is no relationship between the stigmatization of Arabic radicalism and terrorism and learning motivation, and there is a positive and significant relationship between religiosity and learning motivation, but both have a significant influence on motivation to learn Arabic. The results of this study provide theoretical implications that the stigmatization of Arabic radicalism and terrorism cannot be a predictor of motivation to learn Arabic. At the same time, religiosity can predict motivation to learn Arabic. As for the practical implications, which is how to motivate students to learn Arabic, it can be used to overcome the stigmatization of radicalism and terrorism in Arabic with meaningful perceptions and by continuously internalizing religiosity.